IMPLEMENTASI BUDAYA SEKOLAH UNTUK MENUMBUHKAN NILAI-NILAI KARAKTER SISWA SEKOLAH DASAR DI SDN CINANGGERANG I KABUPATEN SUMEDANG - Agi Hamdani; Leli Halimah (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2023)
This research discusses the implementation of school culture as a means to shape the character values ​​of students at at SD Negeri Cinangerang I. The topics of study in this research are: (1) What is the description of school culture at Cinanggerang I Public Elementary School, (2) How is the implementation of school culture in at SD Negeri Cinangerang I in shaping student character values. The research method used in this study is a qualitative method. Sources of data from this study are school principals, teachers, and students. Data collection techniques used are interviews, observation and documentation. The results of the study show that (1) the school culture applied at SD Negeri Cinangerang I is religious culture, 5S culture, literacy culture, environmental care culture. (2) The application of the school culture is carried out through consistent good habituation in both intra-curricular and extra-curricular activities. (3) The character values ​​that are developed through school culture are religious, tolerance, discipline, responsibility, friendship, social care, love to read, care for the environment, love the motherland.